1975
DOI: 10.1021/bi00696a015
|View full text |Cite
|
Sign up to set email alerts
|

Mode of inhibition of Herpes simplex virus DNA polymerase by phosphonoacetate

Abstract: Phosphonoacetate is a highly specific inhibitor of herpes simplex virus-induced DNA polymerase. Sensitivity of herpesvirus type 1 or type 2 induced DNA polymerase to the drug was similar. However, DNA polymerases from other sources such as the host cells (Wi-38), Micrococcus luteus, and hepatitis B virus were highly resistant. In addition, Escherichia coli RNA polymerase and reverse transcriptase of Rous sarcoma virus were also insensitive to the drug. Enzyme kinetic studies showed that inhibition was noncompe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
0

Year Published

1979
1979
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(59 citation statements)
references
References 20 publications
1
58
0
Order By: Relevance
“…We first examined the transcription of viral genes as a function of viral DNA replication. Cells were infected with the wild-type strain HSV-1 KOS1.1 in the presence or absence of phosphonoacetic acid, a specific inhibitor of the viral DNA polymerase (37). Transcription was assayed in nuclei pre- The film was preflashed and exposed at -70°C for 24 hr with an intensifying screen.…”
Section: Resultsmentioning
confidence: 99%
“…We first examined the transcription of viral genes as a function of viral DNA replication. Cells were infected with the wild-type strain HSV-1 KOS1.1 in the presence or absence of phosphonoacetic acid, a specific inhibitor of the viral DNA polymerase (37). Transcription was assayed in nuclei pre- The film was preflashed and exposed at -70°C for 24 hr with an intensifying screen.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years several compounds have been described which are all endowed with selective anti-herpes properties. These compounds include phosphonoacetic acid (3,4), phosphonoformic acid (5, 6), 9-f3-D-arabinofuranosyladenine (araA) (7,8), 5-iodo-5'-amino-2',5'-dideoxyuridine (AIDDU) (9, 10), 9-(2-hydroxyethoxymethyl)guanine (acycloguanosine) (11,12), 1-f3-D-arabinofuranosylthymine (araT) (13,14), 5-iodo-and 5-bromo-2'-deoxycytidine (15, 16), 5,6-dihydro-5-azathymidine (17,18), and erythro-9-[3-(2-hydroxynonyl)]adenine (EHNA) (19). Among the 5-substituted 2'-deoxyuridines, various compounds-namely, 5-methylamino-dUrd (20), 5-methoxymethyl-dUrd (21), 5-propyl-dUrd (22), and 5-propynyloxy-dUrd (23)-proved more inhibitory to herpes than to any other DNA (or RNA) virus.…”
mentioning
confidence: 99%
“…The major DBP is encoded as an E gene product (Quinlan et al, 1984), that is transcription and translation occur before virus DNA synthesis. To study the kinetics of network formation, cells were infected with HSV-2 in the presence of AraA or PAA, conditions known to inhibit virus DN A synthesis (Mao & Robishaw, 1975), after which the distribution of the major DBP was studied. Immunofluorescence studies showed that in the absence of virus DNA synthesis the formation of the network was inhibited.…”
Section: Network Formation Requires Dna Synthesismentioning
confidence: 99%